Effect of extracted phycocyanin by-products as a synbiotic supplement on the production performance and intestinal morphology of broilers - Kannikar Hamprakorn; Buaream Maneewan; Wantamas Jantasin; Mohd Nizam Lani; Tossapol Moonmanee; Julakorn Panatuk (Veterinary World)
Background and Aim: The extracted phycocyanin by-products retain nutritional value, including proteins, polysaccharides, and bioactive compounds, which have the potential as feed supplements in broiler production. This study aimed to evaluate the effect of by-products acquired during phycocyanin extraction, which is used as a novel synbiotic supplement, on the production performance and intestinal health of broilers in a tropical climate.